View of Reykjavík harbor - Árnason, Helgi; Reykjavík (Iceland) (North Dakota State University Libraries, Institute for Regional Studies;)
Elevated view looking down upon the Reykjavík harbor and business district. Arnarhóll park visible in the foreground, and Landakotskirkja church visible in the distance. Gelatin silver prints; Photographic postcards; 10 x 15 cm. "107 Reykjavík við. Höfnina." - Printed on front of postcard. Message on back of postcard in Icelandic dated Dec. 16, 1937. It is addressed to Emile Walters and wife. "Með einkarétti. Helgi Árnason, Hveragerði, Iceland" - printed on back of postcard. Title supplied by staff.